(untitled) (Revista Direito em Debate, 2020)
The central issue of the present article it is about the effects and outcomes of the epistemological closure to historical knowledge in the formation of jurists in Law courses, both in legal teaching and legal research. As research technique it was used the literature review of seminal papers and books about the state of affairs of legal teaching and research in the last decades, just as the personal experience of the authors as university professors in Law courses. Initially it is pointed out organizing elements of a normative and uncritical legal tradition that gives a superficial consideration, or doesn’t consider at all historical, sociological, philosophical and anthropological knowledge. After that are examined some effects in teaching and research of the conjugation of a normative and uncritical legal formation with the contempt or indifference towards historical studies and human sciences in general – called of historical common sense of jurists, to paraphrase Luis Alberto Warat. Some of the effects are the manualization and schematization of Law, the methodological and theoretical reductionism of legal research and a technical and bureaucratic legal ethos. The notes are not reduced to the conclusion part. Along the article are highlighted some evidences of the consequences of a lack of critical comprehension by the jurists about themselves as an historical e social agent placed a field constituted and constitutive of the brazilian social formation.